Delinquent behaviors in group sports: Predictive variables for athletes and fans - Thoma, Maria; Ioannou, Myria; Stavrinides, Panayiotis (Psychology: the Journal of the Hellenic Psychological Society, 2020)
A considerable number of delinquent behaviors presented by young people do happen in the context of sport events. The present study aims to (a) examine the impact of the involvement in an athletic team, either as a fan or as an athlete, on delinquent behaviors and (b) investigate team identification as a predictive factor of the involvement in delinquent behaviors. The study followed a cross-sectional design. The participants were 222 participants with a mean age of 23,5 years who completed a self-report questionnaire measuring the extent of involvement in sports and sport events, the levels of general delinquent behaviors outside of sport events and delinquent behaviors in sport events, and the degree of team identification. Based on the regression analyses performed, the present study supports that both athletes and fans were significantly involved in delinquent behaviors happening in the context of sport events. Being identified with your team was a statistically significant predictor of the delinquent behaviors of fans, even for those with low overall delinquency outside of sport events. The findings of the present study have practical implications and the discussion emphasizes on the need to develop suitable, research-informed interventions to reduce delinquent behaviors taking place in sport events.